2021
DOI: 10.1111/jce.15268
|View full text |Cite
|
Sign up to set email alerts
|

Perimitral atrial tachycardias dependent on residual nonligament of Marshall conduction

Abstract: Introduction: Catheter ablation for perimitral atrial tachycardia (PMAT) that persists despite lateral mitral isthmus (LMI) ablation is challenging. The aim of this study was to identify the role of the ligament of Marshall (LOM) in PMATs that persist after LMI conduction block has been created, and evaluate the validity of ethanol infusion into the vein of Marshall (VOM) as treatment.Methods and Results: Sixteen consecutive PMATs in 13 patients that persisted despite apparent LMI conduction block, which was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This could partially explain why in our study, the AF-free success rate did not show statistical improvement after the implementation of the empirical MVEI strategy (78.9% vs. 7 6.3%, log-rank P = 0.334). However, ultrahigh-resolution mapping and entrainment pacing along the MA demonstrated that about two-thirds of the perimitral ATs were MV-dependent ( 28 ). Addition of MVEI to CA could reduce the incidence of AT recurrence when patients underwent empirical ethanol infusion (95.8% vs. 81.6%, log-rank P = 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…This could partially explain why in our study, the AF-free success rate did not show statistical improvement after the implementation of the empirical MVEI strategy (78.9% vs. 7 6.3%, log-rank P = 0.334). However, ultrahigh-resolution mapping and entrainment pacing along the MA demonstrated that about two-thirds of the perimitral ATs were MV-dependent ( 28 ). Addition of MVEI to CA could reduce the incidence of AT recurrence when patients underwent empirical ethanol infusion (95.8% vs. 81.6%, log-rank P = 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…PMAT is an inhomogeneous diagnosis including those involving only the endocardial aspect of MI, VOM-dependent, and those utilizing non-MB epicardial connections. 25 In our study, we did not specifically classify the PMAT into these groups since high-density mapping was not routinely used, and as the local electrogram in VOM was absent, we were unable to directly verify the involvement of an epicardial connection and record the effect of EIVOM. In the future, techniques that can facilitate detailed activation mapping, including the activation of epicardial structures, should be developed.…”
Section: Limitationmentioning
confidence: 97%